Competitive Effects Hinder the Recolonization of Native Species in Environments Densely Occupied by One Invasive Exotic Species - Michelan, Thaisa S.; Thomaz, Sidinei M.; Bando, Fabielle M.; Bini, Luis M. (Frontiers in Plant Science, 2018)
The responses of native plants to competition with invasive plants depend mainly on the density of the invasive plants and on the ability of the native plants to compete for resources. In this study, we tested the influence of the invasive exotic Urochloa arrecta (Poaceae) on the early colonization of two native species (Pontederia cordata and Leersia hexandra) of aquatic macrophytes. Our hypotheses were (i) the competitive effects of U. arrecta on the native species P. cordata and L. hexandra are density-dependent and that (ii) these species respond differently to competitive interactions with the invasive species. We conducted the experiments in a greenhouse and in the field, in a tropical reservoir. The biomass of U. arrecta (ranging from 206.2 g to 447.1 g). was manipulated in the greenhouse in trays with different densities. After the establishment of the invasive species, we added P. cordata and L. hexandra propagules to each tray. In the field, a propagule of P. cordata was planted in 36 sites with different densities of U. arrecta. The biomass and length of the natives and the biomass of the invasive species were measured in the greenhouse and in the field experiments. The biomass and length of the native plants decreased with increasing biomass of the exotic species in both experiments, showing that the competition between U. arrecta and native species depends on the density of the exotic species. The root:shoot ratio of L. hexandra decreased with increasing U. arrecta biomass, but the opposite occurred for P. cordata. These results indicate that native species exhibit different strategies of biomass allocation when interacting with U. arrecta. The strong competitive effects of U. arrecta and the different responses of the native species help to explain the reduced diversity of native macrophytes observed in sites colonized by U. arrecta. The results also suggest that in a scenario of dominance of exotic species, recolonization by native macrophytes is unlike to occur naturally and without human interventions that reduce the biomass of the exotic species.